2008
DOI: 10.1017/s0007114507797064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome in Chinese adolescents

Abstract: Since national figures on the occurrence of metabolic syndrome among Chinese adolescents are lacking, this study aims to estimate its prevalence and distribution among Chinese youngsters. The 2002 China National Nutrition and Health Survey is a nationally representative cross-sectional study. Applying the criteria for US adolescents, we estimated the prevalence of metabolic syndrome among 2761 adolescents aged 15 to 19 years. The prevalence of metabolic syndrome among Chinese adolescents overall was 3·7 % (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 21 publications
6
43
3
Order By: Relevance
“…Urban residence and high income were positively associated with MetS risk in our study, which was in accordance with other studies [11,19,20]. Generally, these 2 situations mean higher socioeconomic level, which is in line with the risk of many chronic diseases in developing countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Urban residence and high income were positively associated with MetS risk in our study, which was in accordance with other studies [11,19,20]. Generally, these 2 situations mean higher socioeconomic level, which is in line with the risk of many chronic diseases in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…It is increasing rapidly in all ages and is considered one of the important public health challenges in China [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach results in balance among food group intakes, it does not consider controlled energy consumption [39]. In addition, previous studies have shown that the prevalence of MetS is higher in overweight adolescents, compared to those with normal BMI [8,34,40]. Therefore, lack of any significant association between HEI-2005 and MetS might be potentially related to the inability of this index to control the effect of over-consumption, and hence overweight and large waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of metabolic syndrome in this study was lower than previously report from Chinese adults and was similar to Chinese adolescents. 11,12 It was because of a positive effect of age on the prevalence of metabolic syndrome. 13,14 Abdominal obesity, elevated blood pressure and low HDL-C were common components of the metabolic syndrome in this sample.…”
Section: Discussionmentioning
confidence: 99%